2013
DOI: 10.1016/j.yhbeh.2013.03.018
|View full text |Cite
|
Sign up to set email alerts
|

Testosterone influences spatial strategy preferences among adult male rats

Abstract: Males outperform females on some spatial tasks, and this may be partially due to the effects of sex steroids on spatial strategy preferences. Previous work with rodents indicates that low estradiol levels bias females toward a striatum-dependent response strategy, whereas high estradiol levels bias them toward a hippocampus-dependent place strategy. We tested whether testosterone influenced the strategy preferences in male rats. All subjects were castrated and assigned to one of three daily injection doses of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(39 citation statements)
references
References 97 publications
(188 reference statements)
2
35
1
Order By: Relevance
“…The comparable effects of supplementing GDX rats with TP or E suggest that the significant behavioral deficits induced in all of these domains by GDX stem at least in part from a loss of estrogen and/or estrogen metabolites. These findings contradict earlier studies from this lab where GDX-induced deficits in acquisition of T-maze (Kritzer et al, 2001) and operant spatial lever press tasks (Kritzer et al, 2007) were attenuated in GDX rats supplemented with TP but not with E. Although the dose and duration of hormone replacement have been shown to impact spatial cognition in GDX and gonadally intact male rats (Clark et al, 1995; Gibbs, 2005; Goudsmit et al, 1990; Spritzer et al, 2013), these factors were similar across studies and are thus unlikely to underlie the disparities in outcomes. Similarly, while Barnes maze testing has been shown to have minimal effects on rats' corticosterone levels (Harrison et al, 2009), rats in the prior studies were acclimated to handling, apparatus, and were subject to weeks-long testing, suggesting that cross-study differences in animals' stress responses may also have been minimal.…”
Section: Discussioncontrasting
confidence: 96%
See 1 more Smart Citation
“…The comparable effects of supplementing GDX rats with TP or E suggest that the significant behavioral deficits induced in all of these domains by GDX stem at least in part from a loss of estrogen and/or estrogen metabolites. These findings contradict earlier studies from this lab where GDX-induced deficits in acquisition of T-maze (Kritzer et al, 2001) and operant spatial lever press tasks (Kritzer et al, 2007) were attenuated in GDX rats supplemented with TP but not with E. Although the dose and duration of hormone replacement have been shown to impact spatial cognition in GDX and gonadally intact male rats (Clark et al, 1995; Gibbs, 2005; Goudsmit et al, 1990; Spritzer et al, 2013), these factors were similar across studies and are thus unlikely to underlie the disparities in outcomes. Similarly, while Barnes maze testing has been shown to have minimal effects on rats' corticosterone levels (Harrison et al, 2009), rats in the prior studies were acclimated to handling, apparatus, and were subject to weeks-long testing, suggesting that cross-study differences in animals' stress responses may also have been minimal.…”
Section: Discussioncontrasting
confidence: 96%
“…These include animals' ages (Bimonte-Nelson et al, 2003; Kanit et al, 2000) and hormone status, including the duration and dose of hormone deprivation and replacement (Bimonte and Denenberg, 1999; Daniel et al, 2006; Galea et al, 2001; Goudsmit et al, 1990; Spritzer et al, 2011; Spritzer et al, 2013). In addition, evidence for a male preference in utilization of hippocampal-dependent place strategies (Blokland et al, 2006; Hawley et al, 2012) and for high levels of testosterone in males and high levels of estrogen in proestrus females in biasing animals to use place rather than response strategies in solving spatial mazes (Korol et al, 2004; Spritzer et al, 2013) identify animals' approaches as yet another factor likely to influence outcomes, particularly across studies using mazes and testing contingencies where advantage is differentially conferred for place, response, or other strategies (Faraji et al, 2010; Gibbs and Johnson, 2008; Healy et al, 1999; Lund and Lephart, 2001; Ruprecht et al, 2013). …”
Section: Introductionmentioning
confidence: 99%
“…Male rats castrated at pre-puberty period had lower levels of testosterone than sham-castrated rats and showed better spatial learning (shorter escape latency and traveled distance) than the sham-castrated males at the same age in MWM [55]. A low testosterone dose (0.125 mg) in castrated adult male rats caused a significant increase in the use of a cued-response strategy relative to control males [56]. While it is unclear whether testosterone directly regulates spatial learning, evidence suggested that optimal testosterone level affects spatial learning in males.…”
Section: Sex Differences In Cognitionmentioning
confidence: 99%
“…Three weeks after orchidectomy, drugs were subcutaneously administered for seven (7) days behind the neck scruff. Testosterone doses were selected based as the previously reported doses [19,20]. Animals were divided into the following groups with n=6 per group: conditions.…”
Section: Animals and Hormones Treatmentmentioning
confidence: 99%